PENGEMBANGAN DISASTER RECOVERY PLAN MENGHADAPI PANDEMI - Ika Romadoni Yunita; Nailis Syafi’ah (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
Disaster Recovery Plan (DRP) is a set of documents that defines every activity, action and procedure that disaster recovery must carry out, continue business processes in a short time and can save assets in information systems during a pandemic. The final result produced is a Disaster Recovery Plan (DRP) document which contains guidelines for carrying out stages in disaster recovery, policies for carrying out activities, procedures for carrying out activities and forms to fill in the information obtained in recovering when faced with a pandemic using the NIST SP 800-34 standard.